1954
DOI: 10.1063/1.1740135
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal and Molecular Structure of B5H11

Abstract: The molecular structure of B5H11 has been determined from 299 x-ray diffraction maxima which have been analyzed by three-dimensional Fourier and least-squares methods. There are four molecules in a monoclinic unit cell, in the space group P21/n, having parameters a=6.76, b=8.51, c=10.14A, and β=94.3°. Although no molecular symmetry is demanded by the space group, the molecular dimensions indicate C8 symmetry for the isolated molecule. The boron skeleton is a fragment of the icosahedronlike arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…To compare with 1 , we decided to investigate the interactions of two systems that, relative to each other, should display quite opposing degrees of multicenter bonding nature. The interaction between a boron (B1) and hydrogen (H7) atom in diborane, 2 in Figure , is well‐known as consisting of a large degree of multicenter character . However, the interaction between carbon atoms C9 and C12 in n ‐butane, 3 in Figure , which is representative of a classic single covalent CC bond, provides an example of a bicentric interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare with 1 , we decided to investigate the interactions of two systems that, relative to each other, should display quite opposing degrees of multicenter bonding nature. The interaction between a boron (B1) and hydrogen (H7) atom in diborane, 2 in Figure , is well‐known as consisting of a large degree of multicenter character . However, the interaction between carbon atoms C9 and C12 in n ‐butane, 3 in Figure , which is representative of a classic single covalent CC bond, provides an example of a bicentric interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Despite such conceptual difficulties, a large number of interactions have been formally classified (by a multitude of methods) as multicenter bonds. For instance, the remarkable differences observed between the structures of B 2 H 6 and C 2 H 6 led to the discovery of a large number of diborane structures with multicenter bonds . Moreover, multiple ligands which can bridge metal–metal bonds—such as chlorine atoms or carbonyl ligands—have been discovered and are well‐known examples of formal M⋅⋅⋅X⋅⋅⋅M multicenter bonds .…”
Section: Introductionmentioning
confidence: 99%
“…=(0, 1.70, 2.12) (~, r/, 0=(0, 2.12, 2.81) A, error 0.52. Lavine & Lipscomb (1954) solved this structure, and refinement to R=0.106 was done by Moore, Dickerson & Lipscomb (1957). The present refinement reduced R to 0.093, a significant improvement on the 2~o level, and the new coordinates are given in Table 2.…”
Section: B9h15mentioning
confidence: 99%
“…~ Fo, and w = 1 when 4 Fmin. >__ Fo (Lavine & Lipscomb, 1954) were used in most of our studies except as described below.…”
Section: Remarks On Least-squares Proceduresmentioning
confidence: 99%
“…Unfortunately, the Fourier method of computing standard deviations (Hughes & Lipscomb, 1946;Cruickshank, 1949) is not usually modified to include weights related in at least a general way to standard deviations of the observations. We have found that a leastsquares refinement of AgN03 cyclooctatetraene with weights, as described by Lavine & Lipscomb (1954), gave standard deviations less by a factor of two than the standard deviations obtained from a similar refinement of the same compound but with the use of unit weights at every stage of the calculation, including the probable error computation. If the errors are truly random, it is a well-known result of the least-squares procedure that the 'best' system of weighting gives the lowest standard deviations.…”
Section: (D) Errorsmentioning
confidence: 99%